Análisis y evaluación del desempeño en la matriz del banco de Loja S.A. - Iñiguez Maldonado, Thalía Elivanny (2015)
Organizations, in order to survive in a competitive global environment, require their employees consistently high levels of performance. Thus, the performance evaluation plays a key role in the reward system. With this process the employee performance is evaluated, this information is shared with them and ways to improve their results are devised. On this basis, currently employees of an organization are considered or at least be regarded as essential parts of organizational development. Hence the importance of knowing how to recognize his weaknesses but above all their strengths in order to empower them and improve them in favor of the same institution and all who are part of it. In this research the performance evaluation to the parent of the Bank of Loja was made, which once analyzed by the method of graphic scales, with the expectation of an optimal value of 10/10 was reached the following results Performance: Unit Planning and Institutional Development, Total average 7.99; Unit Risk Management, 8.28 average total; Business unit 8.07; Administrative Finance Unit, 8.61; 7.91 Marketing Unit; Operating unit Front 8.33; Back operating unit 9.06; Unit Health and safety 8; 8.25 compliance unit; Human talent unit 8.25; 9.21 unit systems; which focuses primarily on a low level of knowledge of the organizational structure of the Bank of Loja; Negotiation and closing does not have optimal results for the commercial management of products and services and finally have an average level of staff training to ensure their permanence and good performance of activities. Once detected the needs of human talents of the Bank of Loja, whose information has been collected directly from middle management, actions leading to improved performance and the bank as a whole are recommended, For which it is done a training proposal to improve the performance of employees of the Bank of Loja and its positive influence on the organization, its respective planning